2008
DOI: 10.1029/2007rs003775
|View full text |Cite
|
Sign up to set email alerts
|

Focal waveforms for various source waveforms driving a prolate‐spheroidal impulse radiating antenna (IRA)

Abstract: [1] Impulse radiating antennas (IRAs) are designed to radiate very fast pulses in a narrow beam with low dispersion and high field amplitude. For this reason they have been used in a variety of applications. IRAs have been developed for use in the transient far-field region using parabolic reflectors. However, in this paper we focus in the near field region and develop the field waveform at the second focus of a prolate-spheroidal IRA. Certain skin cancers can be killed by the application of a high-amplitude e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…These two conditions led us to use an inhomogeneous, partially lossy dielectric lens. In a previous paper, Altunc et al [] demonstrated that a multilayer dielectric lens can be used to match the impedance from air to tissue. The lens consists of five layers of different dielectric materials with dielectric constants varying in an exponential profile from air to the innermost layer, ϵ rmax .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two conditions led us to use an inhomogeneous, partially lossy dielectric lens. In a previous paper, Altunc et al [] demonstrated that a multilayer dielectric lens can be used to match the impedance from air to tissue. The lens consists of five layers of different dielectric materials with dielectric constants varying in an exponential profile from air to the innermost layer, ϵ rmax .…”
Section: Resultsmentioning
confidence: 99%
“…While ns pulses are delivered with electrodes [Silve et al, ], delivering ultrashort electrical pulses with antennas to biological targets becomes attractive in reaching deep targets. One such antenna is an impulse radiating antenna that relies on a prolate spheroidal reflector [Baum, ; Altunc et al, ; Kumar et al, ]. At the first focus of this reflector, a transverse electromagnetic (TEM) wave launcher projects the EM waves to the reflector; from there they are redirected into the second focus.…”
Section: Introductionmentioning
confidence: 99%
“…Two possible solutions were suggested theoretically by Carl Baum, as part of a major research effort undertook by the Frank Reidy Research Center for Bioelectrics at Old Dominion University (USA): an impulse radiating antenna (IRA) operated in air [12], [13], in combination with a complex many layer dielectric lens [14] and another prolatespheroidal reflector, operated underwater [15]. More recently, at the same research center, a dielectric rod antenna was also suggested as a candidate for generating subnanosecond PEFs for the stimulation of neurological tissue [16].…”
Section: Introductionmentioning
confidence: 99%